Nontraditional modes of mechanical ventilation: progress or distraction?. (June 2012) - Turner, David A; Rehder, Kyle J; Cheifetz, Ira M
As technology continues to develop, a wide range of novel and nontraditional modes of mechanical ventilation have become available for the management of critically ill patients. Proportional assist ventilation, neurally adjusted ventilatory assist and adaptive support ventilation are three novel modes of ventilation, which attempt to optimize patient-ventilator synchrony. Improved interactions between patient and ventilator may be important in improving clinical outcomes. Another important priority for mechanically ventilated patients is lung protection, and nontraditional modes of ventilation that may be implemented to minimize ventilator-associated lung injury include airway pressure release ventilation and high-frequency ventilation. Novel and nontraditional modes of ventilation may represent important tools in the critical care environment; however, continued investigation is needed to determine the overall impact of these various approaches on outcomes for mechanically ventilated patients.